Пилильщик макрофия минерва — Macrophya minerva Benson (Hymenoptera, Tenthredinidae) — балканский элемент в фауне Юго-Западной Украины - Ермоленко, В.М. (Вестник зоологии, 1971)
The fact is desctribed of finding the Balkan species of Macrophya minerva Benso n in the south-western Ukraine. Four females of this species are found 18/V 1951 in the environs of the village Dolinskoye, Izmail district of the Odessa region. The females are caught at the moment of additional nutrition on the flowers of Euphorbia L., growing on the south slope of the dry steppe narrow. Previously the species was known by the only female (holotype) from the North- ' Eastern Greece.